PENERAPAN MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PERBANKAN DI INDONESIA - Kurniawan, Umarudin; Anggraini, Depita; Utama, Fikri Rizki (LPPM Universitas Bina Bangsa, 2024)
This research aims to examine the influence of corporate governance mechanisms on company performance. The sample for this research is banking companies listed on the IDX in 2019 - 2021. Data was taken from the company's annual report. Four corporate governance variables, namely the size of the board of directors, the size of the board of commissioners, managerial ownership, and the independent audit committee are used to explain company performance. Regression analysis is used to test the influence of corporate governance mechanisms on company performance. Based on the results of multiple regression analysis, it shows that the size of the Board of Directors and Independent Internal Auditors has a significant effect on banking company performance, while the Size of the Board of Commissioners and Managerial Ownership do not have a significant effect on performance. banking companies listed on the Indonesian Stock Exchange